PENGARUH BOPO TERHADAP ROA PADA BANK SYARIAH PERIODE 2011 S.D 2015 - Ida Zuniarti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
Efficiency in doing business is an important thing. It will give the positive effect for a company, especially bank, by using efficiency. It is one of the key-success measurement in bank management. Concerning about efficiency in bank is the capability of bank management in controlling operational cost towards operational income. This is measured by using ratio of operational cost towards rational income; It is called BOPO.BOPO has an effect on bank performance. The lower BOPO ratio, the higher bank performance, vice versa. Bank management has to control operational cost so that the return stated can be achieved.The aim of this research is to know the effect of BOPO on ROA in Islamic bank in 2011-2015 period, case study in Bank Muamalat Indonesia. Data used is secondary data; those are finance report, especially balance sheet and report of profit and loss. They are downloaded from Bank Indonesia website. The result of research revealed that BOPO had significantly affected ROA in Bank Muamalat Indonesia in 2011 to 2015. With significancy 0.000, less than 0.05, t value counted -18,743. Determinant coefficient (r2) was 99,2%. It means that ROA 99,2%, was determined by BOPO, and the rest, 0,8%, was affected by other factors. Keywords : ROA, BOPO